2023
DOI: 10.1111/trf.17449
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 seroprevalence among blood donors in Uganda: 2019–2022

Abstract: Background The true burden of COVID‐19 in low‐ and middle‐income countries remains poorly characterized, especially in Africa. Even prior to the availability of SARS‐CoV‐2 vaccines, countries in Africa had lower numbers of reported COVID‐19 related hospitalizations and deaths than other regions globally. Methods Ugandan blood donors were evaluated between October 2019 and April 2022 for IgG antibodies to SARS‐CoV‐2 nucleocapsid (N), spike (S), and five variants of the S protein using multiplexed electrochemilu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
3
4
1
Order By: Relevance
“…COVID‐19 seroprevalence reached 90% among the 2022 women cohort. This finding is in agreement with others at a similar time in the continent: serosurveys in Cameroon, Gambia, Uganda and South Africa have reported antibody positivity between 87% and 96% during the Omicron wave 16,17,19,50,54 . Although lower, the 76.5% seroprevalence reported in Kenya by Awandu et al greatly surpasses PCR confirmed cases 25 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…COVID‐19 seroprevalence reached 90% among the 2022 women cohort. This finding is in agreement with others at a similar time in the continent: serosurveys in Cameroon, Gambia, Uganda and South Africa have reported antibody positivity between 87% and 96% during the Omicron wave 16,17,19,50,54 . Although lower, the 76.5% seroprevalence reported in Kenya by Awandu et al greatly surpasses PCR confirmed cases 25 .…”
Section: Discussionsupporting
confidence: 92%
“…Within the 2021 blood donor cohort, seroprevalence reached 61%. This finding is slightly lower than others in the country which have reported up to 70% 13,14,48 and similar to surveys in Somalia, 18 Uganda, 19 Nigeria, 22 Burkina Faso 49 or South Africa 50,51 where antibody detection between 56% and 67% by 2021 has been reported. Although much lower seroprevalence has been estimated in studies in the Republic of the Congo (31.8%) 11 and Gabon (13%), 52 both relied on lateral‐flow rapid immunochromatography tests, which could justify the difference.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations